Microscopic Investigation of the Combined Use of Antibiotics and Biosurfactants on Methicillin Resistant Staphylococcus aureus - Juma, Abulaziz; Lemoine, Patrick; Simpson, Alistair B. J.; Murray, Jason; O’Hagan, Barry M. G.; Naughton, Patrick J.; Dooley, James G.; Banat, Ibrahim M. (Frontiers in Microbiology, 2020)
One current strategy to deal with the serious issue of antibiotic resistance is to use biosurfactants, weak antimicrobials in their own right, with antibiotics in order to extend the efficacy of antibiotics. Although an adjuvant effect has been observed, the underlying mechanisms are poorly understood. To investigate the nature of the antibiotic and biosurfactant interaction, we undertook a scanning electron microscopy (SEM) and atomic force microscopy (AFM) microscopic study of the effects of the tetracycline antibiotic, combined with sophorolipid and rhamnolipid biosurfactants, on Methicillin-resistant Staphylococcus aureus using tetracycline concentrations below and above the minimum inhibitory concentration (MIC). Control and treated bacterial samples were prepared with an immersion technique by adsorbing the bacteria onto glass substrates grafted with the poly-cationic polymer polyethyleneimine. Bacterial surface morphology, hydrophobic and hydrophilic surface characters as well as the local bacterial cell stiffness were measured following combined antibiotic and biosurfactant treatment. The sophorolipid biosurfactant stands alone insofar as, when used with the antibiotic at sub-MIC concentration, it resulted in bacterial morphological changes, larger diameters (from 758 ± 75 nm to 1276 ± 220 nm, p-value=10-4) as well as increased bacterial core stiffness (from 205 ± 46 mN/m to 396 ± 66 mN/m, p-value=5x10-5). This investigation demonstrates that such combination of microscopic analysis can give useful information which could complement biological assays to understand the mechanisms of synergy between antibiotics and bioactive molecules such as biosurfactants.